2014
DOI: 10.1007/s00395-014-0442-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pseudo-phosphorylated rat cardiac troponin T are differently modulated by α- and β-myosin heavy chain isoforms

Abstract: Interplay between the protein kinase C (PKC)-mediated phosphorylation of troponin T (TnT)- and myosin heavy chain (MHC)-mediated effects on thin filaments takes on a new significance because: (1) there is significant interaction between the TnT- and MHC-mediated effects on cardiac thin filaments; (2) although the phosphorylation of TnT by PKC isoforms is common to both human and rodent hearts, human hearts predominantly express β-MHC while rodent hearts predominantly express α-MHC. Therefore, we tested how α- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Previous studies have correlated tension cost to c and demonstrated that both are useful measures of g [11, 12, 35, 36]. Thus similar effects in both these parameters would validate if TnT R97L altered g .…”
Section: Resultsmentioning
confidence: 84%
“…Previous studies have correlated tension cost to c and demonstrated that both are useful measures of g [11, 12, 35, 36]. Thus similar effects in both these parameters would validate if TnT R97L altered g .…”
Section: Resultsmentioning
confidence: 84%
“…Proteins were visualized by staining the gel with Coomassie brilliant blue (R-250; Bio-Rad Laboratories, Hercules, CA). Densitometric analysis of the MHC protein profiles was performed using the ImageJ software (available on the National Institutes of Health web site), as described previously (14,15,30). For assessing the phosphorylation status of sarcomeric proteins, 10 g of standardized NTG and TG mouse heart samples were loaded and ran on a 12.5% small SDS gel.…”
Section: Methodsmentioning
confidence: 99%
“…Small differences in phosphorylation levels of MLC-1 and MLC-2 are not expected to affect our findings because 1) H886 DIVERSE EFFECTS OF TNT-R144W AGAINST ␣-AND ␤-MHC observed differences in contractile parameters (maximal tension, pCa 50 , tension cost, c, b, k tr , etc.) between ␣-and ␤-MHC fibers are similar to those reported by previous studies (10,12,29,30,49); and 2) the effect of TnT R144W is assessed relative to TnT WT in each group, i.e., ␣-MHC ϩ TnT R144W vs. ␣-MHC ϩ TnT WT or ␤-MHC ϩ TnT R144W vs. ␤-MHC ϩ TnT WT .…”
Section: Analysis Of Mhc Composition In Ntg and Tg Mouse Heartsmentioning
confidence: 96%
See 2 more Smart Citations